2012
DOI: 10.1530/jme-11-0149
|View full text |Cite
|
Sign up to set email alerts
|

Growth differentiation factor-15 upregulates interleukin-6 to promote tumorigenesis of prostate carcinoma PC-3 cells

Abstract: Growth differentiation factor-15 (GDF15), a member of the transforming growth factor-b superfamily, is associated with human cancer progress. We evaluated the role GDF15 plays in tumorigenesis of prostate carcinoma PC-3 cells. Results from real-time RT-PCR and ELISA revealed that expression of GDF15 was approximately threefold higher in LNCaP cells than in PC-3 cells. Other prostate cell lines (PZ-HPV-7, CA-HPV-10, and DU145 cells) expressed extremely low levels of GDF15. Stable overexpression of GDF15 in PC-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 46 publications
1
32
0
Order By: Relevance
“…GDF15 is an ubiquitous cytokine that belongs to the family of transforming growth factor-beta [65], which modulates cell proliferation, differentiation, apoptosis, invasion and metastasis [66] and is over-expressed in many types of cancer [6769], especially during the transition from localized to metastatic disease [70–75]. …”
Section: Resultsmentioning
confidence: 99%
“…GDF15 is an ubiquitous cytokine that belongs to the family of transforming growth factor-beta [65], which modulates cell proliferation, differentiation, apoptosis, invasion and metastasis [66] and is over-expressed in many types of cancer [6769], especially during the transition from localized to metastatic disease [70–75]. …”
Section: Resultsmentioning
confidence: 99%
“…First, patients with chronic liver diseases had higher GDF-15 concentrations than patients in the control group, and the patients with more severe liver diseases showed proportionally higher GDF-15 values. To date, studies have reported that a high serum GDF-15 value was related to lymph node metastasis and a low survival rate in endometrial cancers5 and increased incidence of oral leukoplakia, squamous cell carcinoma, and prostate cancer 6,7. Additionally, it was reported as the predicting factor of reoccurrence of colorectal cancer8 and the independent predicting factor of the mortality from cardiovascular diseases 9,10.…”
Section: Discussionmentioning
confidence: 99%
“…6A and B). GDF-15 is an important growth factor for prostate tumor progression and resistance to cytotoxic agents and radiotherapy in prostate cancer and other cancers (36)(37)(38)(39)(40)(41). Upon GDF-15 silencing (Fig.…”
Section: Identification Of Gdf-15 As a Specific Pace4 Substrate And Pmentioning
confidence: 99%